PENGARUH LATIHAN VARIASI SHOOTING TERHADAP KEMAMPUAN SHOOTING PADA PEMAIN SEPAK BOLA - Samsudin; Intan Primayanti; Sukarman (TEACHING AND LEARNING JOURNAL OF MANDALIKA (TEACHER) e- ISSN 2721-9666, 2022)
The purpose of this study was to determine the effect of shooting variations on shooting skills in soccer games for PS Malaju players, Kilo District, Dompu Regency in 2022. The design of this study used an experimental method with data collection techniques using test and measurement techniques. The population in this study were all players of the PS Malaju Club, totaling 23 players with probability techniques. The instrument used is by dividing the goal field into six scoring areas. The top corner is worth 40 points, the bottom corner is worth 50 points, the top half is worth 20 points, the bottom half is worth 10 points with four balls in front of the goal. Players have 15 seconds to kick all four balls towards the goal and record the score. The data analysis technique used in this study uses the Analytical Requirements Test, Normality Test, Homogeneity Test and Hypothesis Testing. Based on the research data, most of the PS Malaju Club players experienced an increase in the shooting variation practice test on their shooting ability. It can be seen that most of the PS Malaju Club players have a large score difference. The difference score is obtained by subtracting the post-test score from the pre-test score. Of the 23 players of the PS Malaju Club, only five players did not experience an increase in shooting variations after doing 2 treatments or 12 times of treatment. The results of the data obtained are with a confidence level = 95% or (α) = 0.05 the number of samples for the experimental club = 23, obtained t-table = 2.073. Based on the calculation results, the average value of the pre-test data was 82.61 while the post-test data obtained a value of 115.65 and t-count = 3.902 with a sig = 0.001 > 40.613 so "Ho is rejected", it can be concluded that there is an average difference The mean is significant between the pre-test data and the post-test data for shooting variations. The results of the regression analysis showed that it was significant 0.00 or P <0.05 and the coefficient of influence was 0.01.